Environmentally friendly composite material for pipeline and preparation method thereof
By adding flat glass fiber and hemp fiber to the nylon 56 composite material, the interface properties are improved, and the problem of low mechanical strength of nylon 56 is solved, achieving better mechanical properties and application breadth.
Patent Information
- Application Number
- CN202411701000.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-26
AI Technical Summary
The low mechanical strength of nylon 56 limits its wide application in the high-end market.
By adding flat glass fiber and hemp fiber as composite reinforcement fiber fillers, the properties of the glass fiber interface with nylon 56 are improved, thereby improving the mechanical properties of the composite material.
The mechanical properties of composite materials, including strength and toughness, are improved, forming a strong interface, suitable for use as pipeline material.
Smart Images

Figure JY6RU9OP7AFY4G3L22UMDNXDLYGKKKI2996BOTNT 
Figure TBGHBNEK9BSU79ZRC7YGC0KGL4JR1YBE9JHCSEDY
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite materials, and in particular relates to an environmentally friendly composite material for pipelines and a preparation method thereof. Background Art
[0002] Composite materials are materials with two or more phase structures formed by physical and chemical combination of two or more materials with different properties. One material is used as the matrix and the other material is used as the reinforcement. The various materials complement each other in performance, produce synergistic effects, and there are obvious interfaces between the component materials, so that the comprehensive performance of the composite material is better than the original component materials and meets various requirements. This type of material not only has better performance than any single material in the composition, but also has unique properties that the single component does not have.
[0003] Among them, polymer composite materials are materials composed of compounds with relatively high molecular weight. Polymer composite materials are lighter than metal materials such as steel and can be processed into shapes that are difficult to process by other methods. They not only maintain the superior properties of polymer materials, but also overcome the disadvantages of low strength of polymer materials. Due to these characteristics, polymer composite materials are widely used in important sectors such as aerospace, aviation, navigation, and road transportation.
[0004] Nylon is one of the most widely used polymer materials. Due to its excellent mechanical properties, chemical stability, and processability, it is used in general industry, automobiles, electronic appliances, and other fields. Most traditional nylons are synthesized from raw materials extracted from petroleum. With the increasing application of nylon, people's demand for nylon products is increasing. In addition, the increasing depletion of non-renewable resources such as petroleum and the enhancement of environmental awareness have seriously affected the development of nylon. Therefore, it is an urgent problem to develop a bio-based polyamide material with good performance in all aspects. Bio-based PA56 is a new material developed by people in recent years. It is an environmentally friendly and renewable material formed by the condensation of 1,5-pentanediamine synthesized by biological methods and adipic acid. Due to its special asymmetric structure, the free carbonyl and amino groups in the molecular chain of PA56 can promote the absorption of water on the surface of the material and internal migration, and the antistatic ability of the material is enhanced. However, PA56 also has significant defects, such as the need to improve its strength and impact resistance, which hinder the widespread application of PA56 in the high-end market. Summary of the invention
[0005] The purpose of the present invention is to prepare an environmentally friendly composite material for pipelines, which overcomes the technical problem of low mechanical strength of nylon 56, has a smooth surface and is suitable for use as a pipeline material.
[0006] The purpose of the present invention is achieved through the following technical solutions:
[0007] An environmentally friendly composite material for pipelines, comprising the following components in parts by weight:
[0008] 75-90 parts of nylon 56, 10-20 parts of maleic anhydride grafted polymer, 20-25 parts of flat glass fiber, 2-10 parts of hemp fiber, 1-10 parts of inorganic nanoparticles, 1-4 parts of coupling agent, 0-3 parts of lubricant, and 0-3 parts of antioxidant; wherein the hemp fiber has a length of 5-10 mm and a diameter of 0.01-0.2 mm.
[0009] In order to improve the mechanical properties of biomass nylon 56, modification by adding glass fiber filler is a common method for polymers. However, the addition of glass fiber filler will have a great impact on the overall performance of the matrix, among which the interface is the key area of the composite material, which is the transition area connecting the glass fiber and the matrix, and its performance is very different from that of the bulk resin. The performance of nylon 56 composites depends to a large extent on the interface performance. Without a good interface, the synergistic effect between glass fiber and matrix cannot be achieved. The added glass fiber changes the structure and properties of the nylon matrix, especially near the glass fiber filler, which leads to the deterioration of the mechanical properties of nylon 56 composites due to the poor compatibility of glass fiber and nylon resin. How to improve the properties of the interface between glass fiber and nylon 56 is the key to improving the mechanical properties of composites.
[0010] In order to overcome the technical problem of poor compatibility of ordinary glass fibers, the present invention adds flat glass fibers and hemp fibers as composite reinforcing fiber fillers. Flat glass fibers have better dispersibility than ordinary round glass fibers, and have lower shrinkage and smaller warpage than round glass fibers; the melt flow performance of flat glass fiber composite materials is better, and can provide better fluidity, increase spiral flow, reduce friction and viscosity, and optimize processing technology. In order to further improve the fluidity of flat glass fibers and overcome the defect of low toughness of glass fiber reinforced composite materials, the present invention adds hemp fibers of a certain length. Among many natural plant fibers, hemp fibers have the longest fiber length, low density, high crystallinity, longitudinal degree and longitudinal elastic modulus, and are suitable as reinforcing fibers for nylon 56 composite materials. Moreover, hemp fibers have more surface active groups than synthetic fibers such as ultra-high molecular weight polyethylene fibers and aramid fibers, and have good compatibility with resins. Due to the good flexibility of hemp fibers, flat glass fibers present a special-shaped structure, which is conducive to the mutual entanglement of composite fibers composed of flat glass fibers and hemp fibers, and improves the dispersibility of flat glass fibers in resins and the interfacial bonding force between flat glass fibers and nylon resins. Flat glass fibers, hemp fibers and nylon resin matrix are entangled with each other to form a strong interface, which can increase the mechanical properties of fiber composite materials. Fiber-reinforced composite materials made of flat glass fibers and hemp fibers have a better balance of mechanical properties than single fiber-reinforced composite materials. When they have good strength, their toughness will also be improved. Mixing hemp fibers with flat glass fibers can broaden the industrial application of hemp fiber-reinforced composite materials.
[0011] Furthermore, the maleic anhydride grafted polymer is at least one of PP-g-MAH, PE-g-MAH, POE-g-MAH, and EPDM-g-MAH.
[0012] Furthermore, the ratio of the major diameter to the minor diameter of the flat glass fiber is 2-10; the length of the flat glass fiber is 1-15 mm. The cross-sectional shape of the flat glass fiber with a flat cross section can be an ellipse, the major diameter is the maximum length passing through the center point, and the minor diameter is the minimum length passing through the center point.
[0013] Furthermore, the hemp fiber is at least one of sisal fiber, ramie fiber, flax fiber and jute fiber.
[0014] Furthermore, the inorganic nanoparticles are at least one of nano titanium dioxide, nano calcium carbonate, nano silicon dioxide and nano zinc oxide. The addition of inorganic nanoparticles can play a role in strengthening and toughening, further improve the mechanical properties and processing properties of the nylon 56 resin composite material, and improve the floating fiber phenomenon.
[0015] Furthermore, the coupling agent is at least one of a silane coupling agent, a titanate coupling agent, and an aluminate coupling agent. By adding the coupling agent, the compatibility of the flat glass fiber and the inorganic nanoparticles with nylon 56 is further improved, and uneven dispersion of the inorganic filler is prevented.
[0016] Furthermore, the lubricant is at least one of silicone powder, oleamide, erucamide, ethylene bis stearamide, and stearate.
[0017] Furthermore, the antioxidant is at least one of a hindered phenol antioxidant, a phosphite antioxidant, and an aromatic amine antioxidant.
[0018] On the other hand, the present invention also provides a method for preparing an environmentally friendly composite material for a pipeline, comprising the following steps:
[0019] (1) Weigh each component according to the proportion;
[0020] (2) uniformly mixing nylon 56, maleic anhydride grafted polymer, inorganic nanoparticles, coupling agent, lubricant, and antioxidant to obtain a premix;
[0021] (3) The premix is fed into a twin-screw extruder from a main feed port, and the flat glass fiber and hemp fiber are fed into the twin-screw extruder from a side feed port, and the extrusion is performed to form pellets, thereby obtaining an environmentally friendly composite material for pipes.
[0022] Furthermore, the screw speed of the twin-screw extruder is 300-500 r / min, and the extrusion temperature is 265-280°C.
[0023] Compared with the prior art, the technical solution of the present invention brings about the beneficial effects: natural hemp fiber reinforced composite materials have been widely used in engineering materials due to their environmental friendliness, low cost and high toughness, but their mechanical properties are poor. Flat glass fiber, as one of the representatives of inorganic rigid fibers, has excellent mechanical properties and chemical stability, but its high cost and low toughness limit its further application. The present invention adds flat glass fiber and hemp fiber as composite reinforcing fiber fillers. Flat glass fiber has better dispersion ability than ordinary round glass fiber. Due to the good flexibility of hemp fiber, flat glass fiber presents a special-shaped structure, which is conducive to the mutual entanglement of composite fibers composed of flat glass fiber and hemp fiber, improves the dispersibility of flat glass fiber in resin and the interface bonding force between flat glass fiber and nylon resin. The fiber-reinforced composite material manufactured by two kinds of fibers, flat glass fiber and hemp fiber, has a better balance in mechanical properties than single fiber-reinforced composite materials, and its toughness will also be improved when it has good strength. DETAILED DESCRIPTION
[0024] The following examples are given to illustrate the present invention in more detail. It is necessary to point out that the following examples cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technical personnel skilled in the art based on the above-mentioned content of the present invention still fall within the scope of protection of the present invention.
[0025] Example 1
[0026] An environmentally friendly composite material for pipelines, comprising the following components in parts by weight:
[0027] 75 parts of nylon 56, 13 parts of maleic anhydride grafted polymer, 20 parts of flat glass fiber, 4 parts of hemp fiber, 1 part of inorganic nanoparticles, 1 part of coupling agent KH550, 1 part of lubricant, and 1 part of antioxidant 1010; wherein the hemp fiber has a length of 5 mm and a diameter of 0.1 mm; the maleic anhydride grafted polymer is PP-g-MAH; the ratio of the major diameter to the minor diameter of the flat glass fiber is 4, that is, the major diameter is 28 μm, the minor diameter is 7 μm, and the fiber length is 3 mm; the hemp fiber is sisal fiber; the inorganic nanoparticles are nano titanium dioxide; and the lubricant is silicone powder.
[0028] Example 2
[0029] An environmentally friendly composite material for pipelines, comprising the following components in parts by weight:
[0030] 90 parts of nylon 56, 16 parts of maleic anhydride grafted polymer, 25 parts of flat glass fiber, 7 parts of hemp fiber, 10 parts of inorganic nanoparticles, 4 parts of coupling agent KH550, 3 parts of lubricant, and 3 parts of antioxidant 1010; wherein the hemp fiber has a length of 10 mm and a diameter of 0.1 mm; the maleic anhydride grafted polymer is PE-g-MAH; the ratio of the major diameter to the minor diameter of the flat glass fiber is 4, that is, the major diameter is 28 μm, the minor diameter is 7 μm, and the fiber length is 3 mm; the hemp fiber is sisal fiber; the inorganic nanoparticles are nano calcium carbonate; and the lubricant is silicone powder.
[0031] Example 3
[0032] An environmentally friendly composite material for pipelines, comprising the following components in parts by weight:
[0033] 75 parts of nylon 56, 16 parts of maleic anhydride grafted polymer, 20 parts of flat glass fiber, 7 parts of hemp fiber, 10 parts of inorganic nanoparticles, 3 parts of coupling agent KH550, 2 parts of lubricant, and 3 parts of antioxidant 1010; wherein the hemp fiber has a length of 8 mm and a diameter of 0.1 mm; the maleic anhydride grafted polymer is EPDM-g-MAH; the ratio of the major diameter to the minor diameter of the flat glass fiber is 4, that is, the major diameter is 28 μm, the minor diameter is 7 μm, and the fiber length is 3 mm; the hemp fiber is sisal fiber; the inorganic nanoparticles are nano-silicon dioxide; and the lubricant is zinc stearate.
[0034] Example 4
[0035] An environmentally friendly composite material for pipelines, comprising the following components in parts by weight:
[0036] 80 parts of nylon 56, 14 parts of maleic anhydride grafted polymer, 22 parts of flat glass fiber, 5 parts of hemp fiber, 3 parts of inorganic nanoparticles, 2 parts of coupling agent KH550, 1 part of lubricant, and 1 part of antioxidant 1010; wherein the hemp fiber has a length of 7 mm and a diameter of 0.1 mm; the maleic anhydride grafted polymer is EPDM-g-MAH; the ratio of the major diameter to the minor diameter of the flat glass fiber is 4, that is, the major diameter is 28 μm, the minor diameter is 7 μm, and the fiber length is 3 mm; the hemp fiber is sisal fiber; the inorganic nanoparticles are nano-silicon dioxide; and the lubricant is silicone powder.
[0037] Example 5
[0038] An environmentally friendly composite material for pipelines, comprising the following components in parts by weight:
[0039] 88 parts of nylon 56, 15 parts of maleic anhydride grafted polymer, 24 parts of flat glass fiber, 6 parts of hemp fiber, 8 parts of inorganic nanoparticles, 4 parts of coupling agent KH550, 3 parts of lubricant, and 2 parts of antioxidant 1010; wherein the hemp fiber has a length of 8 mm and a diameter of 0.1 mm; the maleic anhydride grafted polymer is POE-g-MAH; the ratio of the major diameter to the minor diameter of the flat glass fiber is 4, that is, the major diameter is 28 μm, the minor diameter is 7 μm, and the fiber length is 3 mm; the hemp fiber is sisal fiber; the inorganic nanoparticles are nano-silicon dioxide; and the lubricant is calcium stearate.
[0040] Example 6
[0041] An environmentally friendly composite material for pipelines, comprising the following components in parts by weight:
[0042] 80 parts of nylon 56, 10 parts of maleic anhydride grafted polymer, 23 parts of flat glass fiber, 6 parts of hemp fiber, 5 parts of inorganic nanoparticles, 2 parts of coupling agent KH550, 2 parts of lubricant, and 2 parts of antioxidant 1010; wherein the hemp fiber has a length of 8 mm and a diameter of 0.1 mm; the maleic anhydride grafted polymer is POE-g-MAH; the ratio of the major diameter to the minor diameter of the flat glass fiber is 4, that is, the major diameter is 28 μm, the minor diameter is 7 μm, and the fiber length is 3 mm; the hemp fiber is sisal fiber; the inorganic nanoparticles are nano zinc oxide; and the lubricant is zinc stearate.
[0043] Example 7
[0044] An environmentally friendly composite material for pipelines, comprising the following components in parts by weight:
[0045] 80 parts of nylon 56, 20 parts of maleic anhydride grafted polymer, 23 parts of flat glass fiber, 6 parts of hemp fiber, 5 parts of inorganic nanoparticles, 2 parts of coupling agent KH550, 2 parts of lubricant, and 2 parts of antioxidant 1010; wherein the hemp fiber has a length of 8 mm and a diameter of 0.1 mm; the maleic anhydride grafted polymer is POE-g-MAH; the ratio of the major diameter to the minor diameter of the flat glass fiber is 4, that is, the major diameter is 28 μm, the minor diameter is 7 μm, and the fiber length is 3 mm; the hemp fiber is sisal fiber; the inorganic nanoparticles are nano zinc oxide; and the lubricant is zinc stearate.
[0046] Example 8
[0047] An environmentally friendly composite material for pipelines, comprising the following components in parts by weight:
[0048] 80 parts of nylon 56, 14 parts of maleic anhydride grafted polymer, 23 parts of flat glass fiber, 2 parts of hemp fiber, 5 parts of inorganic nanoparticles, 2 parts of coupling agent KH550, 2 parts of lubricant, and 2 parts of antioxidant 1010; wherein the hemp fiber has a length of 8 mm and a diameter of 0.1 mm; the maleic anhydride grafted polymer is POE-g-MAH; the ratio of the major diameter to the minor diameter of the flat glass fiber is 4, that is, the major diameter is 28 μm, the minor diameter is 7 μm, and the fiber length is 3 mm; the hemp fiber is sisal fiber; the inorganic nanoparticles are nano zinc oxide; and the lubricant is zinc stearate.
[0049] Example 9
[0050] An environmentally friendly composite material for pipelines, comprising the following components in parts by weight:
[0051] 80 parts of nylon 56, 14 parts of maleic anhydride grafted polymer, 23 parts of flat glass fiber, 10 parts of hemp fiber, 5 parts of inorganic nanoparticles, 2 parts of coupling agent KH550, 2 parts of lubricant, and 2 parts of antioxidant 1010; wherein the hemp fiber has a length of 8 mm and a diameter of 0.1 mm; the maleic anhydride grafted polymer is POE-g-MAH; the ratio of the major diameter to the minor diameter of the flat glass fiber is 4, that is, the major diameter is 28 μm, the minor diameter is 7 μm, and the fiber length is 3 mm; the hemp fiber is sisal fiber; the inorganic nanoparticles are nano zinc oxide; and the lubricant is zinc stearate.
[0052] Example 10
[0053] An environmentally friendly composite material for pipelines, comprising the following components in parts by weight:
[0054] 80 parts of nylon 56, 14 parts of maleic anhydride grafted polymer, 23 parts of flat glass fiber, 6 parts of hemp fiber, 5 parts of inorganic nanoparticles, 2 parts of coupling agent KH550, 2 parts of lubricant, and 2 parts of antioxidant 1010; wherein the hemp fiber has a length of 8 mm and a diameter of 0.1 mm; the maleic anhydride grafted polymer is POE-g-MAH; the ratio of the major diameter to the minor diameter of the flat glass fiber is 4, that is, the major diameter is 28 μm, the minor diameter is 7 μm, and the fiber length is 3 mm; the hemp fiber is sisal fiber; the inorganic nanoparticles are nano zinc oxide; and the lubricant is zinc stearate.
[0055] Comparative Example 1
[0056] Its components and proportions are basically the same as those of Example 10, with the only difference being 29 parts of flat glass fiber and 0 parts of hemp fiber.
[0057] Comparative Example 2
[0058] Its components and proportions are basically the same as those of Example 10, with the only difference being 0 parts of flat glass fiber and 29 parts of hemp fiber.
[0059] Comparative Example 3
[0060] The components and proportions are substantially the same as those of Example 10, except that the length of the hemp fiber is 2 mm.
[0061] Comparative Example 4
[0062] The components and proportions are substantially the same as those of Example 10, except that the length of the hemp fiber is 16 mm.
[0063] Comparative Example 5
[0064] The components and proportions are substantially the same as those of Example 10, with the only difference being that round-section glass fibers are used to replace the flat glass fibers; the round-section glass fibers have a diameter of 10 μm and a fiber length of 3 mm.
[0065] The above embodiment and the comparative example have the same preparation process, comprising the following steps:
[0066] (1) Weigh each component according to the proportion;
[0067] (2) uniformly mixing nylon 56, maleic anhydride grafted polymer, inorganic nanoparticles, coupling agent, lubricant, and antioxidant to obtain a premix;
[0068] (3) The premix is added into a twin-screw extruder from a main feed port, and the flat glass fiber and hemp fiber are added into the twin-screw extruder from a side feed port, and the extrusion is performed into pellets to obtain an environmentally friendly composite material for pipes; the screw speed of the twin-screw extruder is 400 r / min, and the extrusion temperature is 275°C.
[0069] Performance test: The environmentally friendly composite materials for pipes obtained in the examples and comparative examples were prepared into standard samples, and the tensile strength of the samples was tested according to ISO 527-2 standard; the bending strength of the samples was tested according to ISO 178 standard; and the notched impact strength of the samples was tested according to ISO 179 standard. The surface condition of the samples was observed and the surface smoothness was evaluated as A, B, C, and D; the grades from A to D indicate that the surface is getting rougher. The test results are shown in Table 1 below.
[0070]
[0071]
[0072] It can be seen from the experimental data in Table 1 that flat glass fibers have better dispersibility than ordinary round glass fibers. Due to the good flexibility of hemp fibers, flat glass fibers present a special-shaped structure, which is conducive to the entanglement of composite fibers composed of flat glass fibers and hemp fibers, improving the dispersibility of flat glass fibers in resin and the interfacial bonding force between flat glass fibers and nylon resin. The fiber-reinforced composite material made of flat glass fibers and hemp fibers has a better balance in mechanical properties than single fiber-reinforced composite materials. When it has good strength, its toughness will also be improved. Further, it can be seen from Examples 6-10 that when the maleic anhydride grafted polymer is 13-16 parts or the hemp fiber is 4-7 parts, it is more conducive to improving the mechanical properties of the composite material. The applicant speculates that the maleic anhydride grafted polymer, as a polar polymer, has good compatibility with organic fibers; however, as a nylon resin composite material, the amount of polar polymer and organic hemp fiber should not be too much, otherwise it may cause the melt viscosity to increase, which is not conducive to melt processing and affects the mechanical properties of the composite material. Comparative Examples 1-5 show that the present invention improves the dispersibility of flat glass fibers and improves the surface properties of the product through hemp fibers of a specific length; the special-shaped structure of the flat glass fibers provides a basis for interaction with the hemp fibers. The flat glass fibers, hemp fibers and nylon resin matrix are entangled with each other to form a strong interface, thereby increasing the mechanical properties of the fiber composite material. The fiber-reinforced composite material made of flat glass fibers and hemp fibers has a better balance in mechanical properties than a single fiber-reinforced composite material, and when it has good strength, its toughness will also be improved. Mixing hemp fibers with flat glass fibers can broaden the application of hemp fiber-reinforced composite materials in the pipeline industry.
[0073] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. An environmentally friendly composite material for pipelines, characterized in that: Contains the following components in parts by weight: 80 parts of nylon 56, 14 parts of maleic anhydride grafted polymer, 23 parts of flat glass fiber, 6 parts of hemp fiber, 5 parts of inorganic nanoparticles, 2 parts of coupling agent KH550, 2 parts of lubricant, and 2 parts of antioxidant 1010; wherein the hemp fiber has a length of 8 mm and a diameter of 0.1 mm; the ratio of the major diameter to the minor diameter of the flat glass fiber is 4, that is, the major diameter is 28 μm, the minor diameter is 7 μm, and the fiber length is 3 mm; the hemp fiber is sisal fiber.
2. The environmentally friendly composite material for pipes according to claim 1, characterized in that: The maleic anhydride grafted polymer is at least one of PP-g-MAH, PE-g-MAH, POE-g-MAH, and EPDM-g-MAH.
3. The environmentally friendly composite material for pipes according to claim 1, characterized in that: The inorganic nanoparticles are at least one of nano titanium dioxide, nano calcium carbonate, nano silicon dioxide and nano zinc oxide.
4. The environmentally friendly composite material for pipes according to claim 1, characterized in that: The lubricant is at least one of silicone powder, oleamide, erucamide, ethylene bis stearamide and stearate.
5. The method for preparing the environmentally friendly composite material for pipelines according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) Weigh each component according to the proportion; (2) uniformly mixing nylon 56, maleic anhydride grafted polymer, inorganic nanoparticles, coupling agent, lubricant, and antioxidant to obtain a premix; (3) The premix is fed into a twin-screw extruder from a main feed port, and the flat glass fiber and hemp fiber are fed into the twin-screw extruder from a side feed port, and the extrusion is performed to form pellets, thereby obtaining an environmentally friendly composite material for pipes.
6. The method for preparing the environmentally friendly composite material for pipelines according to claim 5, characterized in that: The screw speed of the twin-screw extruder is 300-500r / min, and the extrusion temperature is 265-280℃.
Citation Information
Patent Citations
Resin composition and molded body using the same
CN101796136A
High-strength composite fiber expansion anti-cracking agent reinforced concrete as well as preparation method and application thereof
CN118851686A